1989
DOI: 10.1088/0953-8984/1/13/013
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity and structure of liquid Al-Ge alloys

Abstract: Aluminium is very reactive with the quartz glass vessel generally used for electrical resistivity measurement cells. In the paper the authors describe a new geometrical arrangement to measure accurately the electrical resistivity of liquid alloys, using an alumina vessel. They give experimental results for the Al1-xGex liquid alloys. This system presents an anomalous concentration-dependent temperature coefficient of the resistivity, with respect to the calculated curves, when using the Faber-Ziman formula wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…1(a) and (b), for pure liquid Ge, the parameter which fits the X-ray experiment is A Ge % 0, while A Ge % 1 is a better choice for neutron data. In addition, we note that the good agreement between the present local model and the X-ray experiment for pure Ge is in line with earlier findings that the structure factor of this metal is well described by local as well as non-local models [2,18]. Moreover the modern ab initio molecular dynamics approaches, depending on the authors, showed either better agreement with the X-ray diffraction data or with neutron diffusion data [5][6][7].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1(a) and (b), for pure liquid Ge, the parameter which fits the X-ray experiment is A Ge % 0, while A Ge % 1 is a better choice for neutron data. In addition, we note that the good agreement between the present local model and the X-ray experiment for pure Ge is in line with earlier findings that the structure factor of this metal is well described by local as well as non-local models [2,18]. Moreover the modern ab initio molecular dynamics approaches, depending on the authors, showed either better agreement with the X-ray diffraction data or with neutron diffusion data [5][6][7].…”
Section: Resultssupporting
confidence: 90%
“…The corresponding partial pair correlation functions are calculated using the Monte Carlo method and the partial structure factors are obtained by Fourier transform. In order to compare the theory with neutron experiments [18], the total structure factors are calculated from the Faber-Ziman definition of the structure factors S ij :…”
Section: Resultsmentioning
confidence: 99%
“…Electrical resistivity of Al was studied many times, but a range of reported electrical resistivity data is very large [10][11][12]. The present electrical conductivity values taken from our previous work [13] are very close to the values reported in [14] (converted from resistivity) and agree generally with [14] within a total experimental uncertainty ±2 %.…”
Section: Resultssupporting
confidence: 78%
“…Results on Al-base alloys have been reported. [4,5] For the calculation of the thermal conductivity using the Wie-demann±Franz law the value of the Lorenz number is needed. Experimental results of measurements on metal melts [6,7] have shown that the Lorenz number can be assumed to be close to the theoretical value of Sommerfeld because in the liquid state of metals the heat transport is dominated by free electrons.…”
mentioning
confidence: 99%